Implementing a Resource-Based Relative Value Scale Fee Schedule for Physician Services - Barbara O. Wynn, Hangsheng Liu, Andrew Mulcahy, Edward N. Okeke, Neema Iyer, and Lawrence S. Painter (RAND Corporation, 2013)
California Senate Bill 863 requires that the administrative director (AD) of the Division of Workers’ Compensation implement a resource-based relative value scale (RBRVS) fee schedule to establish maximum allowable amounts for physician and other practitioner services under the California workers’ compensation system. The Department of Industrial Relations asked the RAND Corporation to provide technical assistance in implementing the fee schedule. This report replaces earlier working papers.1 It models the transition policies and impact of implementing the RBRVS fee schedule according to the policies in the AD’s notice of modification to text of proposed regulations (first 15-day comment period) issued on August 2, 2013. The report should be of interest to the California provider and payer communities and to policymakers in California and in other states that are considering implementing a resource-based physician fee schedule for medical services provided to injured workers.